PELAKSANAAN PEMBELAJARAN BERBASIS TEKS DI SMA NEGERI KOTA PADANG - Diana, Putri; Atmazaki, Atmazaki,; Hafrison, Mohammad (Universitas Negeri Padang, 2018)
ABSTRACTÂ The purpose of this research is four, that is describing the process of implementation of text based learning in stage (1) the preparation of context, (2) modeling, (3) making text together, (4) making the text independently in SMA Negeri Padaang. This type of research using qualitative method. Techmique of data collecting is dones by observation, interview, and documentation study. The result of the research shows that teacher in SMA Negeri Padanghave implemented four aspects of text based learning that is in context complilation phase, the teacher ensures the students have understood the meaning of text, the type of text, the form of text, the purpose of the text, and language of the text. At the modeling stage, teacher ensure students are able to analyze the type of the text, text structure, text form, text purpose, and textual language. At the joint text making stage, the teacher ensures that student have been able to organize the text together. At the stage of making the text independently, the teacher ansures the student is able to produce new texts by the students independently.Â Kata kunci : teks, konteks, pemodelan, bersama, mandiri